The girls she left behind [compact disc, unabridged] : a Lizzie Snow novel - Graves, Sarah, 1951- (Dreamscape Media, LLC, 2016)
A teenage girl with a history of running away has dropped out of sight again. The locals and the law both think Tara Wylie is up to her old tricks, until her mother receives a terrifying text message. Equally disturbing, Henry Gemerle, a kidnapper and rapist who once held three girls prisoner for fifteen years, has escaped, and may be lurking in Bearkill. Lizzie Snow teams up with her boss Sheriff Cody Chevrier to search for the missing girl and the wily fugitive. Following a trail of grisly clues - a bloodstained motel room, a makeshift coffin in a shallow grave - Lizzie is drawn ever closer to the flames in her race to save an innocent and corner a monster.